Students’ Experiences in Using English Movies to Improve Students’ Speaking Skills - Rahmah, Lia Nur Affida; Pranata, Mohammad Sofyan Adi (Universitas Pahlawan Tuanku Tambusai, 2024)
This research analyzed the students' experiences using English movies to improve their speaking skills at SMA Nurul Jadid. The research design was descriptive-qualitative, and the participants were three students in year 11 of SMA Nurul Jadid. The data was obtained through in-depth interviews. After collecting the data, the researcher conducted analyses. The findings showed that the students mostly responded positively. The findings indicated that English major students are aware that they can improve their speaking skills by watching English movies. In response, the students expect more educational movies to be published that can supplement their education. Therefore, it can be concluded that using movies has contributed to improving the students' English-speaking skills.